Use of Mebix in psychiatry and general medicine: relevance, prospects, case studies - Olga V. Kotova; Vladimir E. Medvedev; Elena S. Akarachkova; Anton A. Belyaev (LLC "MEDIAFORMAT", 2024)
Anxiety disorders, except the manifestations of anxiety itself, are characterized by a broad spectrum of cognitive and somatic symptoms significantly reducing the individual's quality of life and increasing the risk of somatic disorders. The rate of cardiovascular, respiratory, gastrointestinal, and other disorders throughout life is significantly higher in people suffering from anxiety. Furthermore, many symptoms of anxiety and panic/fear mimic manifestations of somatic disorders. Optimal treatment of anxiety disorders includes both pharmacological and psychotherapeutic interventions. At the same time, psychotherapy is not always available for patients, and internists not always decide to prescribe psychotropic medication, for example antidepressants. In such situations, nonbenzodiazepine anxiolytics showing high efficacy and tolerability can be used. Mebix, having an adaptogenic effect on the central nervous system and a stabilizing effect on the autonomic nervous system, that affects almost all neurotransmitters can be considered one of such drugs. The paper reports clinical cases of patients with anxiety disorders, who were treated with Mebix as monotherapy or in combination with antidepressants.